Sing to me - Browner, Jesse (Little, Brown and Company, 2025)
After the fall of Troy, an eleven-year-old boy sets off for the razed city when his father and sister vanish into the war zone; this "gorgeously drawn" novel offers an intimate vision of the most storied war in history, as seen through the eyes of a child. His family farm and the surrounding community now emptied by war, young Hani embarks on an epic quest -- assisted by a brooding yet brilliant donkey -- to find his lost sister in the ruins of Troy. Some war stories transcend time and circumstance, and so it is with the resourceful and heartbroken Hani, who must employ every bit of intelligence, every scrap of ingenuity, and ultimately every ounce of his spirit and humor to withstand the forces of civilization's collapse. Hani is no ordinary boy, however, and a character unlike any you've ever met. His interior world is one of startling depth and complexity. His insights into life, lives, and history are breathtakingly fresh. And his hope for survival--not a given, and in fact, less than likely--will propel you to the startling conclusion of this brief, elegiac, and singular work. --